The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1515/jpem-2016-0139
|View full text |Cite
|
Sign up to set email alerts
|

Glycemic variability predicts inflammation in adolescents with type 1 diabetes

Abstract: Background Adolescents with type 1 diabetes (T1D) have increased risk of cardiovascular disease as well as elevations in biomarkers of systemic inflammation, plasma protein oxidation and vascular endothelial injury. It is unclear whether hyperglycemia itself, or variations in blood glucose are predictors of these abnormalities. Methods This study was designed to determine the relationship of inflammatory (C-reactive protein, CRP), oxidative (total anti-oxidative capacity, TAOC) and endothelial injury (solubl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
1
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(24 citation statements)
references
References 40 publications
1
20
1
2
Order By: Relevance
“…25,26 It is worth mentioning that although absolute HbA1c levels were used as indicators of glycemic control, glucose variability was not measured in this study. Hoffman et al reported on 17 adolescents with type 1 diabetes, stating that increased glucose variability is associated with increased inflammation in this group, 43 suggesting that pathogenesis in type-1 diabetes is different from T2D. It would be interesting to determine whether patients in the non-controlled glycemia group had increased instances of intermittent hyperglycemia or whether it was sustained hyperglycemia.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…25,26 It is worth mentioning that although absolute HbA1c levels were used as indicators of glycemic control, glucose variability was not measured in this study. Hoffman et al reported on 17 adolescents with type 1 diabetes, stating that increased glucose variability is associated with increased inflammation in this group, 43 suggesting that pathogenesis in type-1 diabetes is different from T2D. It would be interesting to determine whether patients in the non-controlled glycemia group had increased instances of intermittent hyperglycemia or whether it was sustained hyperglycemia.…”
Section: Discussionmentioning
confidence: 97%
“…Many studies in human adults have found no association between glucose variability and consequences of inflammation, such as microvascular or macrovascular complications, arterial stiffness, and carotid intimal thickness. 43 On the other hand, other studies stated that fluctuations in glucose, especially during post prandial periods, heightened the triggering effect on oxidative stress compared to sustained hyperglycemia. 45 The major strength of this study is the stringent procedure we used for the selection of the participants to rule out any acute response to inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…The role of GV as a risk factor for developing complications of diabetes remains controversial, however, several reports associate GV with oxidative stress and damage to susceptible organs [15,16] and chromosomes [17]. Consequently, preventing excessive glucose fluctuations early in the disease course could provide long-term benefit for children.…”
Section: Discussionmentioning
confidence: 99%
“…The activity of intercellular adhesion molecule 1 (ICAM-1), present on leukocytes and endothelial cells, may be increased by a number of cytokines [66]. Soluble forms of ICAM-1 (sICAM-1) constitute a biomarker of endothelial damage and inflammation [67]. Elevated levels of sICAM-1 are found in autoimmune conditions, including T1DM [65,66].…”
Section: Cell Adhesion Moleculesmentioning
confidence: 99%